Does the Five Facet Mindfulness Questionnaire measure what we think it does? Construct validity evidence from an active controlled randomized clinical trial - Goldberg, Simon B. (Psychol Assess, 2015)
The current study attempted a rigorous test of the construct validity of a widely used self-report measure of dispositional mindfulness, the Five Facet Mindfulness Questionnaire (FFMQ), within the context of an active controlled randomized trial (n = 130). The trial included three arms: mindfulness-based stress reduction (MBSR), an active control condition that did not include instruction in mindfulness meditation (Health Enhancement Program, HEP), and a waitlist control condition. Partial evidence for the convergent validity of the FFMQ was shown in correlations at baseline between FFMQ facets and measures of psychological symptoms and psychological well-being. In addition, facets of the FFMQ were shown to increase over the course of an MBSR intervention relative to a waitlist control condition. However, the FFMQ failed to show discriminant validity. Specifically, facets of the FFMQ were shown to increase over the course of the HEP intervention relative to the waitlist control condition. MBSR and HEP, in contrast, did not differ in changes in FFMQ score over time. Implications of these findings for the measurement and theory of mindfulness and MBSR are discussed.